Pelagibacterium lacus sp. nov., isolated from lake water. Issue 6 (17th April 2019) - Liu, Bang-Tao; Wang, Chong; Wang, Xiao-Man; Chen, Guan-Jun; Du, Zong-Jun
Abstract : A Gram-stain-negative, strictly aerobic, oxidase- and catalase-positive, non-gliding, motile with a single polar flagellum, and short rod-shaped bacterial strain, designated XYN52 T, was isolated from a freshwater lake in the west of China. Phylogenetic analysis of the 16S rRNA gene determined that strain XYN52 T was a member of the genus Pelagibacterium within the family Hyphomicrobiaceae . Strain XYN52 T was able to grow at 4–37 °C (optimum, 30 °C), pH 6.0–9.0 (pH 7.5) and in the presence of up to 7.0 % w/v NaCl (0.5 %).The major quinone was ubiquinone 10. The major cellular fatty acids were C18 : 1 ω6 c /C18 : 1 ω7 c, C19 : 0 ω8 c cyclo and 11-methyl C18 : 1 ω7 c . The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol and three kinds of glycolipids. The genomic DNA G+C content was 64.5 mol%. On the basis of these data, strain XYN52 T represents a novel species in the genus Pelagibacterium, for which the name Pelagibacterium lacus sp. nov. is proposed. The type strain is XYN52 T (=KCTC 62845 T =MCCC 1H00348 T ).